Assessing Differential Binding of Aggregation-Induced Emission-Based Luminogens to Host Interacting Surface Proteins of SARS-CoV-2 and Influenza Virus–An in silico Approach - Tanneeru, Karunakar; Bhatraju, Naveen Kumar; Bhosale, Rajesh S.; Kalangi, Suresh K. (Frontiers in Microbiology, 2021)
Early detection of asymptomatic cases through mass screening is essential to constrain the COVID-19 transmission. However, the existing diagnostic strategies are either resource intensive, time consuming, or less sensitive, which limits their use in the development of rapid mass screening strategies. There is a clear pressing need for simple, fast, sensitive and economical diagnostic strategy for SARS-CoV-2 screening even in resource limited settings. In the current work, we assessed the In-silco feasibility of directly labelling virus surface proteins using fluorogenic molecules with aggregation-induced emission (AIE) property. Here, we present the results for binding of two such AIE probes, TPE-P and TPE-S, to SARS-CoV-2 spike protein based on in silico docking studies. Our results show that both TPE-P and TPE-S bind to ACE2-binding, and N-terminal domains of SARS-CoV-2 spike protein. Molecular dynamic simulations have revealed specific nature of these interactions. We also show that TPE-P and TPE-S bind to hemagglutinin protein of influenza virus, but the interaction was found to be weak. This difference in interaction strength may affect the emission spectrum of aforementioned AIE probes. Together, these results form a basis for the development of AIE based diagnostics for differential detection of SARS-CoV-2 and influenza viruses. We believe, these In-silico predictions certainly aid in differentially labelling of the both viruses towards the development of rapid detection by AIE probes.